Elastoplastic dynamic constitutive model of concrete with combined effects of temperature and strain rate - Xinyu Kou; Liang Li; Xiuli Du; Xiyao Zheng (Case Studies in Construction Materials, 2023)
This short communication proposed a dynamic constitutive model, which investigated the combined effects of temperatures and strain rates to characterize the mechanical performance of concrete exposed to fire and blast simultaneously. Compared with the existing constitutive models, the proposed constitutive model is relatively simple with uniform series of parameters, and can be more easily applied to the numerical simulation of the dynamic behaviors of concrete. The elastic strain increment expression for concrete was derived from the elastic free energy function, and the plastic strain increment expression was based on the classical plastic theory. Based on Drucker-Prager yield criterion, the yield equation considering the strengthening effect of strain rate was established. The damage criterion was established to characterize the damage caused by various temperatures and strain rates. The stress–strain diagrams of concrete materials with different temperatures (200 °C, 400 °C, 600 °C, and 800 °C) and strain rates (50 s−1-185 s−1) were calculated under the condition of uniaxial dynamic compress and temperature loading. By comparing with the previous test results, it can be concluded that the current constitutive model accurately simulates the mechanical performance of concrete with various temperatures and various strain rates. It provided a theoretical basis for the safety evaluation of concrete engineering structures.